Vacuum production of OTFTs by vapour jet deposition of Dinaphtho[2,3-b:2',3'-f]thieno[3,2-b]thiophene (DNTT) on a lauryl acrylate functionalised dielectric surface - Assender, H; Ding, Z; Abbas, G; Morrison, J; Yeates, S; Patchett, E; Taylor, D (Elsevier, 2016)
Roll-to-roll (R2R) production of organic transistors and circuits require patterned deposition of organic layers at high deposition rate. Here we demonstrate a vapour-jet process for the rapid deposition of the organic semiconductor dinaphtho[2,3-b:2',3'-f]thieno[3,2-b]thiophene (DNTT). The deposition rate achieved, equivalent to ~200 nm/s onto a stationary substrate, was several orders of magnitude faster than ordinary thermal evaporation. Nevertheless, transistor yield was 100% with an average mobility of 0.4 cm2/Vs in a single pass deposition onto a substrate moving at 0.15 m/min. We also demonstrate a vacuum, high rate R2R-compatible process for surfacefunctionalising a gate dielectric layer with lauryl acrylate which enabled an all-vacuum route to the fabrication of a five-stage ring oscillator.